Neonatal cholestasis and biliary atresia: perspective from Malaysia - Lee, Way Seah (Faculty of Medicine, University of Malaya, 2010)
The liver is an important organ of the human body, playing a major role in the metabolism and storage of nutrients, synthesis of protein and other nutrients, as well as detoxifying many metabolic by-products. The response of the foetal and newborn liver to external insult and injury is limited. This is because the ability of the closely interdependent structures of a developing liver of expressing in the face of a variety of insults is limited as well. Thus most infants with insults to the liver present as cholestatic jaundice with variable degree of pale stools, enlarged liver and conjugated hyperbilirubinaemia. Biliary atresia, an idiopathic condition characterized by progressive fibrosing obliteration of both intra- and extrahepatic bile ducts, is the most important cause of neonatal cholestasis worldwide, including Malaysia. It is also the most important indication for childhood liver transplantation the world over. Challenges facing infants with biliary atresia include a delay in the diagnosis and late surgery, leading to a poor outcome. This often results from a failure to recognise the potential serious nature of an infant with prolonged cholestatic jaundice and pale stools among health care professionals